Effects of Modified Atmosphere Packaging and Chitosan Treatment on Quality and Sensorial Parameters of Minimally Processed cv. ‘Italia’ Table Grapes - Giorgia Liguori; Giuseppe Sortino; Gregorio Gullo; Paolo Inglese (Agronomy, 2021)
Table grape is a non-climacteric fruit, very sensitive to water loss and gray mold during postharvest handling and storage. The aim of this work was to evaluate the effects of modified atmosphere packaging and chitosan treatment on quality and sensorial parameters of minimally processed cv. ‘Italia’ table grape during cold storage (14 days at 5 °C) and shelf-life (7 and 14 days of cold storage plus 5 days at 20 °C), reproducing a retail sales condition. Our data showed a significant effect of high CO2-modified atmosphere in combination with chitosan and alone on preserving quality, sensorial parameters, and delaying decay of minimally processed table grape. The most effective treatment in terms of preservation of quality, sensory, and nutritional quality was high-CO2 modified atmosphere packaging plus chitosan treatment. The overall results showed that when a proper modified atmosphere packaging is combined with a postharvest chitosan treatment, gray mold growth can effectively be controlled in ready-to-eat cv. ‘Italia’ table grape and that modified atmosphere packaging (MAP) with high levels of CO2 and reduced concentration of O2 in combination with chitosan treatment could prevent the negative effect of high-CO2 in-packages level, like berry browning and rachis browning and dehydration.